1998
DOI: 10.1056/nejm199806253382601
|View full text |Cite
|
Sign up to set email alerts
|

An Outbreak of Multidrug-Resistant Pneumococcal Pneumonia and Bacteremia among Unvaccinated Nursing Home Residents

Abstract: In this outbreak a single pneumococcal strain was disseminated among the residents and employees of a nursing home. The high prevalence of colonization with a virulent organism in an unvaccinated population contributed to the high attack rate. Clusters of pneumococcal disease may be underrecognized in nursing homes, and wider use of pneumococcal vaccine is important to prevent institutional outbreaks of drug-resistant S. pneumoniae infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
132
1
2

Year Published

2000
2000
2012
2012

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(139 citation statements)
references
References 61 publications
2
132
1
2
Order By: Relevance
“…Pneumococci are often part of the nasopharyngeal flora; especially due to circumstances of crowding, as observed in day-care centers, nursing homes, and hospitals, the risk of being colonized with pneumococci is increased (3,20,27,28). Usually, colonization is not followed by disease, as local barriers at the mucosal level of the respiratory tract and the human immune system are often protective.…”
mentioning
confidence: 99%
“…Pneumococci are often part of the nasopharyngeal flora; especially due to circumstances of crowding, as observed in day-care centers, nursing homes, and hospitals, the risk of being colonized with pneumococci is increased (3,20,27,28). Usually, colonization is not followed by disease, as local barriers at the mucosal level of the respiratory tract and the human immune system are often protective.…”
mentioning
confidence: 99%
“…It is a disease of continuing endemicity particularly in infancy and old age [6]. Day care centres are very likely to be places for spread of organisms in toddlers [7,8,9,10]. In military medical literature, there are accounts of pneumococcal outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Multidrug-resistant strains of Streptococcus pneumonia accounted for 4 of these outbreaks. The largest, involved a 100-bed nursing home in Oklahoma (Nuorti JP, 1998). Eleven of 84 residents (13%) developed pneumonia, and 3 residents died.…”
Section: Others Outbreaksmentioning
confidence: 99%
“…The Author observed that 13% of the residents developed pneumonia, and that the mortality rate was 23%. Resistant isolates were recovered from 64% of residents with pneumonia and from 23% of non infected residents (Nuorti JP & Al, 1998).…”
Section: Penicillin-resistant Pneumococcimentioning
confidence: 99%